Isolation of Chitosan from Lake Toba Freshwater Lobster Shells (Cherax quadricarinatus) - Sinaga, Novita Yulianti; Ridwanto, Ridwanto; Daulay, Anny Sartika; Nasution, Haris Munandar (Pustaka Media Publishing, 2024)
Chitosan is an amine polysaccharide that is formed after chitin undergoes a deacetylation process. This compound has a significant role as a natural biopolymer which is polycationic. This research aims to make chitosan from freshwater lobster shells obtained from Lake Toba. The research method is experimental. Includes making chitosan from freshwater lobster shells. The process of making chitosan includes demineralization, deproteination and deacetylation stages. Chitosan was characterized by measuring water content, ash content, yield, solubility, and analysis using an FTIR spectrophotometer. Based on the results of research that has been carried out, it was found that the characteristics of chitosan have a yield value of 50.88%, water content 5.9%, ash content 0.67% and chitosan dissolves in glacial acetic acid. The results of the research show that chitosan has similar functional groups to standard chitosan and the degree of deacetylation is 80.25%. This research has met the chitosan standard (SNI 7949:2013) with a percentage of the degree of deacetylation of chitosan that meets the standard (>60%).